1989
DOI: 10.1246/bcsj.62.2189
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition in the Formation of Conglomerate Crystal. 2. The Role of Arenesulfonic Acid in the Conglomerate Crystals of Amino Acid Salts

Abstract: The structures of conglomerate crystals, p-chlorobenzenesulfonic acid salt of l-alanine, p-toluenesulfonic acid salt of l-serine, and benzenesulfonic acid salt of l-leucine, were determined by X-ray analysis. The crystals are built up of repeating units consisting of two amine components and two acid components to form a helical column by hydrogen bonds. The arrangements of the arenesulfonic acids are found to be similar to each other in these systems. Moreover, the arrangements have similarity to those of cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…One way around this restriction is by converting a racemic compound into a conglomerate salt: For a series of chiral compounds it has been shown that the probability of forming a conglomerate salt is 2 to 3 times larger than of forming a single component conglomerate . Recently, Spix et al managed to apply Viedma Ripening to racemic amino acid compounds, e.g., dl -Phenylalanine (Phe), via the formation of its conglomerate salt with 2,5-xylenesulfonic acid (XSA). , Their results showed that using a conglomerate forming salt enables the utilization of Viedma Ripening to racemic compounds. This would expand the application range of Viedma Ripening by roughly 10 times, if such conglomerate forming salts exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way around this restriction is by converting a racemic compound into a conglomerate salt: For a series of chiral compounds it has been shown that the probability of forming a conglomerate salt is 2 to 3 times larger than of forming a single component conglomerate . Recently, Spix et al managed to apply Viedma Ripening to racemic amino acid compounds, e.g., dl -Phenylalanine (Phe), via the formation of its conglomerate salt with 2,5-xylenesulfonic acid (XSA). , Their results showed that using a conglomerate forming salt enables the utilization of Viedma Ripening to racemic compounds. This would expand the application range of Viedma Ripening by roughly 10 times, if such conglomerate forming salts exist.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, Spix et al managed to apply Viedma Ripening to racemic amino acid compounds, e.g., DL-Phenylalanine (Phe), via the formation of its conglomerate salt with 2,5-xylenesulfonic acid (XSA). 14,15 Their results showed that using a conglomerate forming salt enables the utilization of Viedma Ripening to racemic compounds. This would expand the application range of Viedma Ripening by roughly 10 times, if such conglomerate forming salts exist.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The effect of anions as conglomerators on the crystal structure of racemates was studied, mostly concerning racemic coordination complexes and limited types of organic racemates were investigated from this point of view …”
Section: Introductionmentioning
confidence: 99%
“…13 The effect of anions as conglomerators on the crystal structure of racemates was studied, mostly concerning racemic coordination complexes [14][15][16][17][18][19] and limited types of organic racemates were investigated from this point of view. [20][21][22][23][24][25][26] The structural and thermoanalytical investigations of the rac-α-phenylethylammonium salts have proved that the hydrogen phthalate and hydrogen malonate anions form racemic compounds, while the hydrogen succinate anion forms a conglomerate, the latter being the only one which could be resolved by preferential crystallization. 22 A comparison of the structures has revealed that the hydrogen bonding network in hydrogen phthalate and hydrogen malonate salts are very similar, while the hydrogen succinate salt is different.…”
Section: Introductionmentioning
confidence: 99%
“…These methods can be applied to the resolution of amino acids as salts with aromatic sulfonic acids, which are known to be conglomerates. 26 The idea of using a deficiency of the conglomerator (Scheme 1) was extended to crystallization with a deficiency of the achiral solubiliser promoting the solubility of the compound to be resolved. As mentioned above, Werner complexes 2 and 3 highly differ in solubility, therefore the Clanion can be considered as a solubiliser, and a spontaneous resolution can be expected when crystallising with its deficiency.…”
mentioning
confidence: 99%